تأثير استخدام طريقة Reciprocal Teaching على قدرة الطلاب في قراءة النصوص العربية لدى طلاب الصف التاسع بمدرسة المتوسطة الحكومية 1 ميدان سومطرة الشمالية - Aulia Rahmah, Aulia Rahmah; Kusmarrabbi karo, Tiy; Sapii Harahap, Muhammad (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
The formulation of the problem in this study is whether there is an influence of the use of the Reciprocal Teaching method on students' ability to read Arabic texts in grade nine students of MTs-N 1 Medan. And the purpose of this study is to determine the influence of the use of the Reciprocal Teaching method on students' ability to read Arabic texts in grade nine students of MTs-N 1 Medan. The method used is a quantitative approach with an experimental method with a true-experimental design, namely Posttest Only Control using statistical data. The results obtained are that there is an influence of the use of the Reciprocal Teaching method on students' ability to read Arabic texts with an average posttest result for the experimental class of 68.5 and an average posttest result for the control class of 45.7, and the results of the t-test with a significant value smaller than 0.05 so that the hypothesis is accepted, meaning that there is an influence of the use of the Reciprocal Teaching method on students' ability to read Arabic texts.